The Influence Of Work Culture, Leadership Patterns And Work Discipline On The Performance Of Police Members At The Intelligence And Security Unit Of The Tanah Laut Police, South Kalimantan Regional Police - Abdullah A. Niam; Nurus Sjamsi (Jurnal Multidisiplin Sahombu, 2022)
Objective This study is to determine and analyze the significant influence of work culture, leadership patterns and work discipline simultaneously and partially on the performance of police members and to determine and analyze the dominant variables on the performance of police members at the Polres Tanah Laut Polda South Kalimantan Satintelkam. Population and samples 50 respondents were members of the Tanah Laut Police Intelligence Unit South Kalimantan Police. Data type quantitative with multiple regression analysis. The results of the study show that work culture, leadership patterns and work discipline have a significant simultaneous effect on the performance of police members, work culture, leadership patterns and work discipline have a significant partial effect on the performance of police members at the Tanah Laut Police Resort Police, South Kalimantan and leadership patterns have a dominant effect on the performance of police members at the Tanah Laut Police Resort Police, South Kalimantan.